STATUS HUKUM RIBA AL-FADL DAN RIBA AN-NASI’AH MENURUT EMPAT MADZHAB - M. Jefriadi Mais; Arkan Maulana Utama; Fatmah Taufiq Hidayat (PT. Saha Kreasi Indonesia, 2026)
This study examines the legal status of two forms of usury, namely usury al-fadl and usury an-nasi'ah, from the perspective of four Islamic schools of jurisprudence: Hanafi, Maliki, Shafi'i, and Hanbali. This study is comparative in nature by analyzing the legal basis, definition, 'illat (legal reasons), scope of application, as well as similarities and differences in views between the four schools. The four schools agree that usury al-fadl and usury an-nasi'ah are absolutely haram based on the text of the Qur'an and the hadith of the Prophet Muhammad SAW. The differences occur in the scope of commodities affected by the law and the 'illat used in the qiyas method. A deep understanding of these two types of usury is very relevant in the context of the development of contemporary Islamic economics and finance.